PREVENTION OF DENTAL CARIES THROUGH DENTAL HEALTH EDUCATION AND UTILIZATION OF MARINE PRODUCTS AT ELEMENTARY SCHOOL MUHAMMADIYAH 9 SURABAYA - Pinasti, Restika Anindya; Pangabdian, Fani; Damayanti, Nurul (LPPM Univ. Ibn Khaldun Bogor, 2025)
Muhammadiyah 9 Elementary School, Surabaya, is geographically located on the coast, so it is often referred to as Bahari Muhammadiyah 9 Elementary School. Based on preliminary survey results, Muhammadiyah 9 Elementary School students frequently consume cariogenic foods, resulting in a high caries index of 4.6. From an educational perspective, the learning method is still relatively conventional and does not align with the